Evolutionarily conserved long intergenic non-coding RNAs in the eye - Mustafi, Debarshi (Oxford University Press, 2013)
The discovery that the mammalian transcriptome encodes thousands of long intergenic non-coding (linc) RNA transcripts, together with recent evidence that lincRNAs can regulate protein-coding genes, has added a new level of complexity to cellular transcriptional/translational regulation. Indeed several reports now link mutations in lincRNAs to heritable human disorders. Here, we identified a subset of lincRNAs in terminally differentiated adult human retinal neurons based on their sequence conservation across species. RNA sequencing of eye tissue from several mammalian species with varied rod/cone photoreceptor content identified 18 lincRNAs that were highly conserved across these species. Sixteen of the 18 were conserved in human retinal tissue with 14 of these also conserved in the macular region. A subset of lincRNAs exhibited restricted tissue expression profiles in mice, with preferential expression in the retina. Mouse models with different populations of retinal cells as well as in situ hybridization provided evidence that these lincRNAs localized to specific retinal compartments, most notably to the photoreceptor neuronal layer. Computational genomic loci and promoter region analyses provided a basis for regulated expression of these conserved lincRNAs in retinal post-mitotic neurons. This combined approach identified several lincRNAs that could be critical for retinal and visual maintenance in adults.